Aplicación del régimen impositivo simplificado ecuatoriano (RISE) y su incidencia en la actividad económica de los comerciantes del mercado mayorista de la ciudad de Ambato a partir de su implementación - Lara Arias, María Teresa (2013)
This thesis is composed by four chapters in which is developed this topic based on generalities like concepts and definitions that will be used for the application of different techniques in this investigation, to achieve the main objective which was explained before.